Wasathiyyah in Practice: Sharia Council Fatwas and the Construction of Moderate Islamic Legal Reasoning in Wahdah Islamiyah - Saban, Syandri; Nurdiana, Nurdiana; Ridwan, Ridwan; Iqbal, Muhammad; Jurdi, Syarifuddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This article investigates the role of fatwa as a medium for institutionalizing wasathiyyah within Wahdah Islamiyah, one of Indonesia’s emerging Islamic movements. While wasathiyyah has been widely discussed in normative and political discourse, its embodiment in organizational fatwas remains underexplored. This study adopts a qualitative case study approach by analyzing fatwas issued by Wahdah Islamiyah’s Sharia Council (Dewan Syariah Wahdah Islamiyah), supported by interviews with council members and document analysis of official publications. The findings reveal that the Council’s fatwas consistently reflect a framework of moderation by balancing three principles: doctrinal orthodoxy (tahqiq al-‘aqidah), social responsibility (maslahah al-‘ammah), and contextual adaptability (murā‘āt al-waqi‘). Fatwas concerning interfaith relations, political engagement, and contemporary socio-economic issues demonstrate a deliberate attempt to avoid both rigid literalism and excessive liberalism. However, tensions also emerge as fatwas navigate between internal expectations of ideological purity and external pressures from a pluralistic society. This study argues that fatwas serve not only as instruments of normative regulation but also as vehicles for embedding wasathiyyah in organizational governance.